2019
DOI: 10.4102/ajod.v8i0.576
|View full text |Cite
|
Sign up to set email alerts
|

The health benefits of exercise therapy for patients with Down syndrome: A systematic review

Abstract: BackgroundMany patients with Down syndrome (PWDS) have poor cardiometabolic risk profiles, aerobic capacities and weak hypotonic muscles, primarily because of physical inactivity and poor diet.ObjectivesThis study discusses the benefits of exercise therapy on body composition, aerobic capacity, muscle strength, proprioception and cardiometabolic profiles of PWDS.MethodsA literature review using the Crossref metadatabase, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…The benefits of increased aerobic work capacity and body composition help reduce the cardiometabolic risk profile of this population. However, more randomized controlled trials of longer duration than the present study are needed to determine the dose-response to exercise and to validate these preliminary empirical findings [ 34 ]. One possible solution to the results obtained in the sample of adolescents with SD could be the development of physical activity programs that target neuromuscular deficits before young people re-deal with exercise as with the non-disabled population [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of increased aerobic work capacity and body composition help reduce the cardiometabolic risk profile of this population. However, more randomized controlled trials of longer duration than the present study are needed to determine the dose-response to exercise and to validate these preliminary empirical findings [ 34 ]. One possible solution to the results obtained in the sample of adolescents with SD could be the development of physical activity programs that target neuromuscular deficits before young people re-deal with exercise as with the non-disabled population [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible solution to the results obtained in the sample of adolescents with SD could be the development of physical activity programs that target neuromuscular deficits before young people re-deal with exercise as with the non-disabled population [ 35 ]. These programmes should focus on the development of strength, endurance, and FMS at an early age as these components are now understood to play an important role in the development of other capacities such as cardiorespiratory, agility or balance [ 34 ]. It has even been shown that strength can play an important role throughout the lives of people with DS as low levels of strength have been associated in lower extremities with an increased risk of falls [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise programs have been tested in DS individuals. These studies suggest health benefits for patients, with improved cardiometabolic risk profile, muscle strength, aerobic capacity, proprioception, and postural stability [ 60 ]. However, another study reported no efficacy of exercise to achieve weight loss in people with DS [ 61 ].…”
Section: Ds and Obesitymentioning
confidence: 99%
“…Também devem ser incluídos nessa rotina exercícios de força envolvendo diferentes grupos musculares (utilizando acessórios alternativos como faixas elásticas, garrafas pet como halteres, e até mesmo o peso do próprio corpo), com pelo menos 8-12 repetições (intensidade moderada), 2 vezes por semana. 10,11 As atividades da vida diária, tais como limpar a casa ou o quintal, subir escadas ou brincar com um animal de estimação também são importantes para manter as pessoas com SD fisicamente ativas e integradas. As atividades físicas devem ser realizadas preferencialmente em um espaço seguro e ventilado.…”
Section: Palavras-chaveunclassified